Cognitive Behaviour Group Counseling with Self-Instruction and Cognitive Restructuring Techniques to Improve Students' Self-Confidence: Array - Evi Kartika Chandra; Mungin Eddy Wibowo; Sunawan Sunawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2019)
The lack of method in improve student self-confidence was the background of this study. The researchers was investigating the effect of Cognitive Behaviour Therapy group counseling with self-instruction and cognitive restructuring techniques to improve students' self-confidence. The research method used was pretest and posttest design quasi-experiment, test design repeated measure ANOVA by involving 16 students as sample who were selected by random sampling from 75 students. The results showed that cognitive restructuring and self-instruction technique is effective to improve the self-confidence. After comparing the the result of both techniques, self-instruction was higher than cognitive restructuring technique to improve students' self-confidence.